Implementation Analysis of Early Detection and Intervention Program for Growth and Development of Children Under Five at Tegal Health Centers - Naharani, Adrestia Rifki; Joebagio, Hermanu; Prayitno, Adi (Indonesian Journal of Medicine, 2016)
Background: The first five years of life is often considered as golden period, ÃÂ critical period, or window opportunity. During this period there is maximal growth and development. Early Detection and Intervention Program for Growth and Development of Children Under Five (SDIDTK) is a program that aims to do early detection and intervention when there is an impairment in growth and development in children under five or pre-school children. Early detection allows early intervention. This study aimed to analyze the implementation of early detection and intervention program for growth and development of children under five.Subjects and Method: This was a qualitative study with case study approach, conducted in Tegal Health Centers, Tegal, Central Java. Nineteen key informants were selected purposely for this study, including health center midwife, midwife who were in charge of coordinating child and adolescents affair, head of the health center,ÃÂ  head of Children and Adolescents Division at District Health Office Tegal, and mothers who had children with growth disorder.Results: SDIDTK has been implemented since 2010. The communication aspect has not been implemented consistently. There was a lack in resources, including personnel, equipment, and ÃÂ infrastructure. The attitude of the program implementer was not positive, because they considered that program was not effective. Guideline book and Standard Operating Procedure (SOP) were available. Growth examination activities were sufficient, but development examination activities were lacking. The reporting system was not sufficiently implemented.Conclusion: SDIDTK program was not been implemented optimally in Tegal. It is sugested to enhance the motivation of the program implementer and improve the equipment and they infrustructure for SDIDTK implementation.Keywords: implementation, SDIDTK program, growth, development, children under fiveCorrespondence:ÃÂ Adrestia Rifki Naharani. Masters Program in Public Health Sebelas Maret University, SurakartaIndonesian Journal of Medicine (2016), 1(3): 175-182https://doi.org/10.26911/theijmed.2016.01.03.05